Semiotics Study of Wayang Character Symbols on the Ceiling of Graha Sahid Surakarta - Rifai, Dian Muhammad; Seftianingsih, Dina Kristiana; Paradita, Dea Syahnas; Rafia, Indy; Pramesti, Vika Dyah (Journal of Contemporary Indonesian Art, 2025)
The interior concept of the Graha Sahid Surakarta room is formed from the ceiling. You can see that the character is very strong with wayang characters. The symbolism of wayang figures in interior design can convey a traditional and artistic atmosphere to the room. This research aims to analyze the description of semiotic studies at the level of signifier and signified originating from the wayang characters symbols on the ceiling at Graha Sahid Surakarta.              The data collection method in this article is the documentation method. Researchers also use a data analysis method called the semiotic analysis method. In carrying out semiotic analysis, researchers used the basic theory of Roland Barthes, namely the meaning of signifiers, signifieds, denotations and connotations of the wayang character symbols on the ceiling at Graha Sahid Surakarta.             The results of the research show that using Roland Barthes' semiotic theory on the wayang characters symbol on the ceiling at Graha Sahid Surakarta provides a deep understanding of how these symbols influence the perception and experience of space. Semiotic analysis will of course pay attention to how the placement of the selected wayang characters can influence the visual narrative of the room by placing the wayang characters in an order and creating a clear storyline. In interior design, wayang character symbols can provide a special emotional feel for the room's users.